Pectoral Fascial (PECS) I and II Blocks as Rescue Analgesia in a Patient Undergoing Minimally Invasive Cardiac Surgery. Issue 6 (November 2017) - Yalamuri, Suraj; Klinger, Rebecca Y.; Bullock, W. Michael; Glower, Donald D.; Bottiger, Brandi A.; Gadsden, Jeffrey C.
Abstract : Introduction: Patients undergoing minimally invasive cardiac surgery have the potential for significant pain from the thoracotomy site. We report the successful use of pectoral nerve block types I and II (Pecs I and II) as rescue analgesia in a patient undergoing minimally invasive mitral valve repair. Case Report: In this case, a 78-year-old man, with no history of chronic pain, underwent mitral valve repair via right anterior thoracotomy for severe mitral regurgitation. After extubation, he complained of 10/10 pain at the incision site that was minimally responsive to intravenous opioids. He required supplemental oxygen because of poor pulmonary mechanics, with shallow breathing and splinting due to pain, and subsequent intensive care unit readmission. Ultrasound-guided Pecs I and II blocks were performed on the right side with 30 mL of 0.2% ropivacaine with 1:400, 000 epinephrine. The blocks resulted in near-complete chest wall analgesia and improved pulmonary mechanics for approximately 24 hours. After the single-injection blocks regressed, a second set of blocks was performed with 266 mg of liposomal bupivacaine mixed with bupivacaine. This second set of blocks provided extended analgesia for an additional 48 hours. The patient was weaned rapidly from supplemental oxygen after the blocks because of improved analgesia. Conclusions: Pectoral nerve blocks have been described in the setting of breast surgery to provide chest wall analgesia. We report the first successful use of Pecs blocks to provide effective chest wall analgesia for a patient undergoing minimally invasive cardiac surgery with thoracotomy. We believe that these blocks may provide an important nonopioid option for the management of pain during recovery from minimally invasive cardiac surgery.